Sharp Force Injuries at the University Hospital of the West Indies, Kingston, Jamaica: A Seventeen-year Autopsy Review - Neblett, A (West Indian Med J, 2014)
OBJECTIVES: This study aimed to ascertain the prevalence and patterns of fatal sharp force injuries, victims' demographics, cause of death and average survival time at the University Hospital of the West Indies (UHWI), Kingston, Jamaica. METHODS: The autopsy records for 1990-2010 were searched for fatal cases of sharp force injuries. The records for 1998-2001were not located. A 17-year retrospective analysis was therefore performed and findings for the two periods, 1990-1997 and 2002-2010 were compared. All data were obtained from the provisional anatomical diagnoses (PAD) autopsy reports. RESULTS: During the 17-year period, 57/4264 autopsies were performed for sharp force injuries, yielding an overall autopsy prevalence rate of 1.34%; 1.25%, 26/2086 (95% CI 0.77, 1.73) in Period 1 and 1.42%, 31/2178 (95% CI 0.92, 1.92) in Period 2. The majority were males (91.1%), in the age group 15-39 years (77%), mean age of 30.9 years (range = 17-65 years). Stab wounds predominated (91.3%) and the chest was the area most frequently stabbed (42.1%). In the 24 fatalities due to chest injuries only, eight (33.3%) had injuries to the heart alone. Forty-five patients (79.0%) died within 24 hours from exsanguination. Injury documentation at autopsy was deficient. CONCLUSION: Stabbing was the most common sharp force injury, mainly involving the chest, and young men were at greatest risk. Most patients died from exsanguination within 24 hours of admission. Introduction of synoptic-type reports for both clinical and autopsy examination may improve documentation.